Data collection process in the complex informational ecology of the Museum of Sexual Diversity - Brito, Jean Fernandes [UNESP] (Univ Federal Santa Catarina, 2025)
Objective: To describe the data collection process within the scope of complex informational ecology, with a specific focus on the analog environments of the Museum of Sexual Diversity. Method: The ethnographic research methodology was adopted, allowing for deep immersion in the museum's context. Results: Through detailed observations, informal conversations, and semi-structured interviews, the researcher captured the dynamic interaction between visitors, staff, and museum exhibits. Conclusions: The collected data contribute to an in-depth analysis of sexual diversity issues and the role of the museum in contemporary society, highlighting the importance of appropriate methodological approaches to understanding the complexity of analog environments such as the Museum of Sexual Diversity.
Keywords: Data collection; Ethnography; Observation; Interview; Complex Informational Ecology; Museum of Diversity